Energy efficiency of platinum-free alkaline direct formate fuel cells. (1st August 2016) - Wang, L.Q.; Bellini, M.; Filippi, J.; Folliero, M.; Lavacchi, A.; Innocenti, M.; Marchionni, A.; Miller, H.A.; Vizza, F.
Highlights: Alkaline Platinum-free formate fuel cells top 42% efficiency @ 60 °C. Palladium efficiently oxidizes formate. Power density exceeding 250 mW cm −2 @ 60 °C has been achieved. Performance exceeds that of Alkaline Direct Alcohol Fuel Cell. Abstract: We report the energy performance of a new platinum-free alkaline direct formate fuel cell, equipped with a commercial anion exchange membrane, a nanostructured Pd/C anode and a Fe–Co/C cathode. The cell was investigated both at room temperature and at 60 °C for the determination of the following parameters: (i) maximum power density, (ii) delivered energy, (iii) faradic (fuel conversion) and energy efficiency. These parameters show a dramatic dependence on fuel composition. The highest energy efficiency is obtained using high energy density fuel (4 M KCOOH and 4 M KOH) and with a maximum operating temperature of 60 °C. This represents a key step in the progress of alkaline platinum-free DFFC technology, demonstrating their potential as power sources for portable electronic devices and remote power generation systems. For example, a fuel load of 750 ml in a DFFC device operating at 60 °C would be able to produce 90 W h of energy, that required to fully charge the battery of a laptop computer.